Green Accounting Impact on Financial Performance of Indonesian Food and Beverage Firms Listed on IDX 2020–2023 - Bunga Indah Bayunitri; Rasi V. Saragih; Irene Sukma Lestari Barus; Tetty Lasniroha (Invoice : Jurnal Ilmu Akuntansi, 2026)
This study investigates the impact of green accounting on the financial performance of food and beverage manufacturing firms listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. Increasing environmental challenges and regulatory pressures have encouraged companies to incorporate environmental costs into their financial reporting systems; however, the adoption of green accounting in Indonesia remains relatively limited. This study employs a quantitative approach using panel data regression analysis. The sample consists of 11 firms selected through purposive sampling, resulting in 44 firm-year observations. Financial performance is proxied by Return on Assets (ROA), while green accounting is measured using the environmental cost ratio, defined as the proportion of corporate social responsibility (CSR) environmental expenditures to earnings after tax. The empirical results reveal that green accounting has a statistically significant effect on financial performance. Firms that allocate and manage environmental costs more efficiently tend to demonstrate higher profitability levels. This finding suggests that integrating environmental considerations into financial decision-making not only enhances operational efficiency but also strengthens corporate reputation and investor confidence. Moreover, the results support legitimacy theory, indicating that companies engaging in environmental responsibility are more likely to gain stakeholder trust, which contributes to improved financial outcomes. Despite its significance, the explanatory power of green accounting remains moderate, implying that other factors also influence financial performance. This study contributes to the literature by providing empirical evidence from an emerging market context and highlights the strategic importance of green accounting in achieving sustainable financial performance. The findings also offer practical implications for managers and policymakers to promote broader adoption of environmentally responsible accounting practices.